DESIGN AND OPTIMIZATION OF SOLID LIPID NANOPARTICLES (SLNs) OF ZOLMITRIPTAN FOR THE MANAGEMENT OF MIGRAINE - Garud, Akanksha; Singh, Deepti; Garud, Navneet (Indonesian Journal of Pharmacy, 2013)
Solid lipid nanoparticles (SLNs) of zolmitriptan were produced by solvent emulsification-diffusion technique. Soya lecithin and poloxamer 188 were used as surfactants and stabilizers of the particles. The formulations were optimized for independent variables (amount of stearic acid, amount of lecithin and homogenization time) in order to achieve desired particle size with maximum percent entrapment efficiency (% EE). Prepared SLNs were characterized by transmission electron microscopy (TEM), atomic force microscopy (AFM) and zeta potential measurements. To achieve our goal, eight formulations (F1–F8) of SLNs were prepared by solvent injection technique and optimized by 23 full-factorial design. The responses of the design were analyzed using Minitab 15. On the basis of software analysis, formulation F8 was selected as optimized formulation and was evaluated for the independent parameters. Optimized formulation showed particle size of 340nm, percent entrapment efficiency (EE) of 81.36 and 79.11% of in-vitro drug release after 24h. The release kinetics of the optimized formulation best fitted the Higuchi model.Key words: solid lipid nanoparticles, zolmitriptan, solvent emulsificationdiffusion technique, in-vitro release.